Avaliação da assistência ao pré-natal na atenção básica no Brasil - FRÓZ, Maryam Andrade (2019)
The study, conducted in the period 2017 to 2018, aimed to evaluate prenatal care in Brazil, based on the Program for Improvement and Access to Basic Care Quality. This is a descriptive, quantitative study, based on secondary data belonging to the 'External Evaluation' component available in the PMAQ-AB bank, 2nd cycle, year 2014, for all Brazilian states. The reference population consisted of professionals of 29,778 Family Health Teams and 9,945 pregnant women users of the 24,055 Basic Health Units evaluated. Indicators of structure, process and results were evaluated, classified as adequate, intermediate and inadequate. In the assessment of the structure, the availability of equipment, printed material and immunobiologicals was classified as adequate. The access and use of prenatal consultations, from the perspective of pregnant women, was classified as an intermediate, and to examinations and procedures as appropriate. It was concluded that the structure and the work process, evaluated by the professionals, were classified as adequate, while the results, observed from the perspective of the pregnant women, were classified as intermediaries.